2008
DOI: 10.1093/ajcn/87.3.517
|View full text |Cite
|
Sign up to set email alerts
|

Is folic acid good for everyone?

Abstract: Fortification of food with folic acid to reduce the number of neural tube defects was introduced 10 y ago in North America. Many countries are considering whether to adopt this policy. When fortification is introduced, several hundred thousand people are exposed to an increased intake of folic acid for each neural tube defect pregnancy that is prevented. Are the benefits to the few outweighed by possible harm to some of the many exposed? In animals, a folic acid-rich diet can influence DNA and histone methylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
445
3
13

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 519 publications
(467 citation statements)
references
References 198 publications
6
445
3
13
Order By: Relevance
“…This is reassuring considering the concern about potential adverse effects, possibly through epigenetic changes, of folic acid fortification of the food supply in the US and elsewhere. 27,28 were deficient in methyl donor nutrients, especially by the second trimester of pregnancy. For example, only 96 (9%) of women had second trimester folate intake <600 μg/d.…”
Section: Resultsmentioning
confidence: 99%
“…This is reassuring considering the concern about potential adverse effects, possibly through epigenetic changes, of folic acid fortification of the food supply in the US and elsewhere. 27,28 were deficient in methyl donor nutrients, especially by the second trimester of pregnancy. For example, only 96 (9%) of women had second trimester folate intake <600 μg/d.…”
Section: Resultsmentioning
confidence: 99%
“…A commensurate increase in erythrocyte folate concentrations was reported in women of reproductive age within two years. 7 What is described as "supra-physiological" levels of circulating folate [8][9][10] has been reported in a quarter of the US population since FA fortification began. 7 Approximately 10% of pregnant women report taking supplements containing FA in doses exceeding 1000 µg per day, the maximum tolerable limit recommended by the Institute of Medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the nature and extent of single-carbon metabolism within these cells are not understood . Given the importance attached to folic acid in the diet of intending mothers aimed, primarily, at reducing the incidence of neural tube defects (Lucock 2000, Smith et al 2008, Osterhues et al 2009, it seems surprising that so little attention has been directed towards understanding its metabolism and that of related B-vitamins by the follicle-enclosed oocyte and pre-implantation embryo. We have previously shown that human embryonic stem cells express transcripts for most of the methyl cycle enzymes illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%